Purificação, caracterização parcial e potencialidade biotecnológica de três lectinas de sementes de espécies de Leguminosae da subtribo Diocleinae - Correia, Jorge Luis Almeida (2015)
Leguminosae is recognized by the large amount of isolated and characterized lectins, especially seeds. In this group stand out proteins extracted from species belonging to subtribe Diocleinae, the number of studies in different areas of knowledge. Lectins can be defined as proteins or glycoproteins which are not originated from a body's immune response and have the ability to recognize and bind reversibly to mono or oligosaccharides particular without, however, altering their chemical structures. Different works in our group are structurally haracterizing these proteins as well as elucidating some possible biotechnological applications for these molecules. In this sense, the objective of this study was to isolate and characterize lectins of different species of Leguminosae of Diocleinae subtribe and test them for toxicity to Artemia sp. naupilos, The effect on the smooth muscle of blood vessels and the detention lectin matrix agarose previously activated with cyanogenic bromide (CNBr). Were isolated and characterized the lectin Dioclea sclerocarpa, Dioclea lasiocarpa and Dioclea lasiophylla. Were also made circular dichroism studies on lectin Dioclea sclerocarpa and Dioclea lasiocarpa. The lectin Dioclea lasiophylla was tested against Artemia sp. order to assess their toxicity and was also immobilized on agarose matrix. We evaluated the effect of lectin Dioclea lasiocarpa in the smooth muscle of blood vessels. The knowledge gained from the three scientific articles published in this thesis is a major breakthrough in this promising field of study that has been continuously growing for biotechnological applications.